Lithium-ion Batteries Modeling and Optimization Strategies for Sinusoidal Alternating Current Heating at Low Temperature. (October 2018) - Li, Jun-qiu; Sun, Danni
Abstract: A thermo-electric coupled model of sinusoidal alternating current (AC) heating for lithium-ion power batteries is proposed in this paper. The model combines the equivalent circuit model with the heat generation model in frequency domain. The model is validated against the experimental results of sinusoidal AC heating with different amplitudes and frequencies of current. An optimal strategy of sinusoidal AC heating based on battery safe operating voltage limit is proposed . It is found that in the high frequency region, the maximum current amplitude under the safety voltage limit is larger, the maximum heat generation rate of the battery is larger, and the battery can be heated from -20°C to 0°C within 480s.